ANALISIS NUMERIK PENGARUH KONFIGURASI LUBANG LINER TERHADAP PERFORMA RUANG BAKAR MESIN TURBIN BERUKURAN KECIL - Fathurisma, Agassi
In this final project the author discusses about numerical analysis of four combustion chamber models that will be considered to be used for gas turbine engine. These models are tubular combustion chamber with curved vane swirler as a flame stabilization method. Curved vane swirler is used in order to achieve a better combustion performance, because this type of swirler will produce a lower pressure drop along the chamber compared to the flat vane swirler. Geometrical variations between models are limited to diffuser shape and liner holes configuration, which includes number of holes, their diameter, and the placement spot along the liner length. The first model’s dimension and specification are based on a calculation that has been done before, while two other models’ are obtained by trial and error method based on first model’s performance. The fourth or the last model’s are obtained using the Lefebvre calculation method. Numerical analysis of all combustion chamber models are done using computational fluid dynamics application named Ansys Fluent. The model with best combustion performance based on numerical simulation will undergo further analysis to obtain its off-design performance, which will be done by varying fuel-air ratio and air mass flow rate that enters the combustion chamber. Simulation results show that relocation of liner holes are not significantly affecting the combustion chamber’s performance. The addition of primary holes reduce pressure loss because of the reduction of air flow throughout the holes, but at the same time also reducing the cooling performance of the dilution holes. Lefebvre calculation method produces the best and most balanced performance result, although more improvements still can be made through further development.